PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS XI SMA NEGERI 3 PADANG - Fajria Oktaviani (Departemen Matematika, 2022)
Mathematical communication ability is basically the main goal of the learning process. However, in reality, the mathematical communication skills of class XI students at SMA Negeri 3 Padang are still low. This is seen by analyzing the answers to mathematical communication skills and it is found that students have not been able to solve the problem. One of the efforts that can be done to overcome these problems is by applying the Think Talk Write type of cooperative learning model. The purpose of this study was to determine whether the mathematical communication skills of students who learn by applying the Think Talk Write (TTW) type cooperative learning model are better than the mathematical communication skills of students who learn by direct learning models in class XI students of SMA Negeri 3 Padang. Keywords – Think Talk Write, Mathematical Communication Ability